Comparative analysis of high-intensity resistance training and blood flow restriction training on enhancing upper limb muscle strength and mass - Zhang, Jianli; Chang, Hualong; Cui, Huijuan; Chen, Biao (Frontiers in Physiology, 2025)
PurposeTo investigate the effects of blood flow restriction training with fixed pressure combined with low-intensity resistance training (BFRT-F) and progressive pressure combined with low-intensity resistance training (BFRT-P) in enhancing upper limb muscle strength and mass, and to compare their effects with high-intensity resistance training (HIRT).MethodsA stratified randomized controlled trial was conducted, where 34 participants were randomly assigned to the HIRT, BFRT-F, and BFRT-P groups. The 8-week intervention included thrice-weekly training sessions.Results1) All groups showed significant 1RM increases, with HIRT and BFRT-P superior BFRT-F. 2) HIRT significantly improved isokinetic muscle strength indicators, including peak torque of shoulder, elbow joints, and trunk and back muscle groups, compared with BFRT-F and, in some measurements, BFRT-P. BFRT-P also significantly increased peak torque compared to BFRT-F. BFRT-F demonstrated significant gains in peak torque for multiple joint flexors and extensors. 3) Muscle circumference increased significantly in HIRT and BFRT-P groups, with the highest gain in HIRT. 4) Only HIRT and BFRT-P significantly increased muscle mass, with HIRT demonstrating the highest growth in both arms.ConclusionThe efficacy hierarchy was HIRT > BFRT-P > BFRT-F. While HIRT is optimal for strength and hypertrophy, BFRT-P is a viable alternative for individuals contraindicated to high-intensity training.